A method and apparatus for measuring a spray area - ZHOU YI (2018)
A method and apparatus for measuring a spray area, the method comprising: obtaining flight data of a drone during a spraying operation; and determining a spray area according to the flight data and aspray area of a spray head configured on the drone for a spray job; the apparatus includes: a memory and a processor; the memory is for storing program codes; and the processor calls the program codesto execute the measurement method when the program codes are executed. The measurement method improves the measurement accuracy of the spray area and also improves the accuracy of the plant protection workload. 种喷洒面积的测量方法和设备，该方法包括：获取无人机在执行喷洒作业的过程中的飞行数据；以及根据所述飞行数据以及无人机上配置的用于喷洒的喷头的喷洒幅度确定喷洒作业的喷洒面积；该设备包括：存储器和处理器；存储器用于存储程序代码；处理器调用所述程序代码，当程序代码被执行时，用于执行所述测量方法。该测量方法提高了喷洒面积的测量准确率，也提高了植保工作量的准确率。